Implementation plans included in World Health Organisation guidelines. (December 2015) - Wang, Zhicheng; Norris, Susan; Bero, Lisa
Abstract Background The implementation of high-quality guidelines is essential to improve clinical practice and public health. The World Health Organisation (WHO) develops evidence-based public health and other guidelines that are used or adapted by countries around the world. Detailed implementation plans are often necessary for local policymakers to properly use the guidelines developed by WHO. This paper describes the plans for guideline implementation reported in WHO guidelines and indicates which of these plans are evidence-based. Methods We conducted a content analysis of the implementation sections of WHO guidelines approved by the WHO guideline review committee between December 2007 and May 2015. The implementation techniques reported in each guideline were coded according to the Cochrane Collaboration's Effective Practice and Organisation of Care (EPOC) taxonomy and classified as passive, active or policy strategies. The frequencies of implementation techniques are reported. Results The WHO guidelines (n = 123) analysed mentioned implementation techniques 800 times, although most mentioned implementation techniques very briefly, if at all. Passive strategies (21 %, 167/800) and general policy strategies (62 %, 496/800) occurred most often. Evidence-based active implementation methods were generally neglected with no guideline mentioning reminders (computerised or paper) and only one mentioning a multifaceted approach. Many guidelines contained implementation sections that were identical to those used in older guidelines produced by the same WHO technical unit. Conclusions The prevalence of passive and policy-based implementation techniques as opposed to evidence-based active techniques suggests that WHO guidelines should contain stronger guidance for implementation. This could include structured and increased detail on implementation considerations, accompanying or linked documents that provide information on what is needed to contextualise or adapt a guideline and specific options from among evidence-based implementation strategies.